A conceptual model of creative activity and personal self-development - Chertakova, Elena M.; Yarovova, T. V.; Opanova, Z.; Lavrova, Galina N.; Kachalova, Ludmila P. (Revista de la Universidad del Zulia, 2020)
Modern socio-economic, political and sociocultural changes are becoming dynamic increasingly: new technologies are being introduced (production, information, etc.), political and state doctrines are changing, alternative sources of public opinion are appearing, scientific knowledge is growing steadily, the volume is expanding information rapidly. The educational system is faced with a fundamentally new task - the search for conditions for the formation of a person who is able to find and create his life and professional path in changing circumstances, overcome the fundamental fragmentation of knowledge, and find his own intellectual and moral integrity and identity. Currently, in the scientific environment, there is a growing interest in studying the organization of creative thinking and self-development of a person in various directions, such as general, social, pedagogical and engineering psychology, etc. The variety of developments in the problem of this process makes it necessary to identify the principles and functions in which ideas about him, and determine its psychological specificity. The article proposes a conceptual model that provides the informal nature of the organization of creative activity and personal self-development. The principles ensuring the unity of the process of their professional and creative development are highlighted. Certain conditions for the organization of educational activities in accordance with the presented concept.